Best Answer

4x2 is 8+ 12x + 3 collect like terms, 8+3= 11, 12x+11 to solve for x, transpose the 11 to the other side of the = sign, 12x=-11, divide by 12, x=-11/12

Q: Solve the equation 4x2 plus 12x plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x2 + 12x + 5 = (2x + 1)(2x + 5).

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2+12x = 4x(x+3) when factored

4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)

4(x + 2)(x + 1)

Related questions

4x2 = -12x, divide both sides by 4x: x = -3

4x2 + 12x + 5 = (2x + 1)(2x + 5).

You need to rivse your question. It appears that there is not an equation here. 4*2+12x+9? You can't really solve this it is more of a statement. You can however simplify it to 12x+17- Whoever wrote this obviously can't read. It's supposed to be 4x^2+12x+9 (2x+3)(2x+3)

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2+12x = 4x(x+3) when factored

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.

12x * 4x2 = 48x3

4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)

(2x+5)(2x+1)

4(x + 2)(x + 1)

4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).

Factor the equation and solve for x in each part. x3-4x2-12x Factor out an x right away x (x² - 4x - 12) factor the trinomial x (x - 6) (x + 2) now solve each for y=0 x=0, (x-6=0), (x+2=0) The zeroes (solutions) to the equation are {-2 0 6 }■